Prevalence of TB-related symptoms and self-reported disability among adult TB survivors - A.K. McDonald; D. Nakkonde; P. Kaggwa; S. Zalwango; A. Joseph; E. Buregyeya; J.N. Sekandi (IJTLD Open)
BACKGROUND: Growing evidence suggests that post-TB-related morbidity occurs often among TB survivors, but there is limited epidemiological data on the burden of symptoms and disability after successful completion of treatment. We evaluated the prevalence of TB-related symptoms, self-reported disability, and factors associated with disability among adult TB survivors who recently completed treatment in Uganda. METHODS: Between January 2022 and October 2023, we conducted a study of adults who completed treatment for drug-susceptible TB in Kampala, Uganda. We collected data on demographics, TB-related symptoms, HIV status, and disability measured using the World Health Organization Disability Assessment Schedule (WHODAS 2.0). RESULTS: Of the 200 participants, the median age was 33.0 years (IQR 26–44.5); 52.5% were male, and 23% were HIV-infected. The prevalence of TB symptoms was 58%, and self-reported disability was 83.5%. Factors significantly associated with disability were having completed treatment within the last 6–8 months and experiencing TB symptoms (aOR 2.87, P = 0.04; and aOR 2.51, P = 0.03, respectively), after adjusting for age, sex and HIV status. CONCLUSIONS: TB-related symptoms and self-reporting of any disability were highly prevalent in the study population. There is a need for further longitudinal evaluation and considerations to expand the continuum of care and support to improve the quality of life for TB survivors post-TB treatment